2017
DOI: 10.1142/s0219581x17500120
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of TiO2Nanoparticles with Polycarbonate and Investigation of its Mechanical Properties

Abstract: In this project, nanocomposite films were prepared with different Titanium dioxide (TiO2) percentages. Properties of polycarbonate (PC) and PC–TiO2 nanocomposite films were studied by X-ray diffraction (XRD) analysis and Fourier transform infrared (FTIR) spectroscopy. The structure of samples was studied by XRD. The mechanical properties of PC–TiO2 nanocomposite films were investigated by conducting tensile tests and hardness measurements. Thermal stability of the nanocomposites was studied by thermogravimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Thermogravimetry (TG) is a technique that measures the mass of a sample against time or temperature. 55,56…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermogravimetry (TG) is a technique that measures the mass of a sample against time or temperature. 55,56…”
Section: Resultsmentioning
confidence: 99%
“…Thermogravimetry (TG) is a technique that measures the mass of a sample against time or temperature. 55,56 The thermogravimetric analysis was performed aer the thermal disintegration of the copper nanoparticle powder. Fig.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…A BUEHLER (model 60044 USA) microhardness tester with a mounted microscope was used to conduct Vickers microhardness testing. TGA curves reveal that TiO 2 nanocomposite films have stronger thermal resistance than polycarbonate films, and this resistance appears to grow as the TiO 2 concentration rises [ 139 ].…”
Section: Characterization Of Bioinorganic Nanomaterialsmentioning
confidence: 99%
“…In a related study, Jahantigh and Nazirzadeh showed the elastic modulus and tensile strength of the composite of polycarbonate (PC) and Titanium oxide (TiO 2 ) nanocomposite increased slightly with increasing weight fraction of nanoparticles. 12 3.3. Scanning electron microscopy Figure 5(a) shows SEM image of PLA15%NC at low resolution.…”
Section: Tensile Testingmentioning
confidence: 99%
“…11 (b) Ceramic and silicate nanoparticles, which include Nano Si, SiO 2 , TiO 2 . 12 (c) Carbon based nanomaterials such as nano carbon (NC) particles, carbon nanotube (CNT) and carbon nano¯ber (CNF). 13 Single walled carbon nanotube (SWCNT) and multi walled carbon nanotube (MWCNT) are commonly used as additives in polymer composites.…”
Section: Introductionmentioning
confidence: 99%